2009
DOI: 10.1016/j.aca.2009.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Determination of plutonium isotopes in waters and environmental solids: A review

Abstract: A number of analytical methods have been developed in the past decades for environmental monitoring of plutonium (Pu) isotopes around nuclear facilities, emergency preparedness as well as for risk assessment of contaminated areas resulting from nuclear weapon tests, nuclear accidents, and the discharge of nuclear waste. This article summarizes and critically compares recently reported methods for determination of Pu isotopes in waters and environmental solid substrates, in which sample pre-treatment is imperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
95
0
6

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(106 citation statements)
references
References 124 publications
0
95
0
6
Order By: Relevance
“…[2] There are a number of analytical methods reported that use ion exchange/extraction chromatography to determine actinides in soil. Hou et al [3] surveyed a wide range of separation methods for Pu in environmental samples. Methods included varied combinations of ion exchange and/or extraction chromatographic techniques.…”
Section: Introductionmentioning
confidence: 99%
“…[2] There are a number of analytical methods reported that use ion exchange/extraction chromatography to determine actinides in soil. Hou et al [3] surveyed a wide range of separation methods for Pu in environmental samples. Methods included varied combinations of ion exchange and/or extraction chromatographic techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Although some automated analysis procedures have been reported for determination of radionuclides like Pu in environmental samples [131], the application of these approaches for 99 Tc determination is still limited and only applied in few laboratories [91,132]. In early 57 studies, the automation of the analysis of 99 Tc is mainly focused on the separation step using anion exchange or extraction chromatography techniques.…”
Section: Automated Analytical Methods For Technetium-99 Determinationmentioning
confidence: 99%
“…For example, 1.2x10 14 Bq of 238 Pu, 2.2x10 16 Bq of 241 Pu and 6.1x10 14 Bq of 239+240 Pu was discharged from the reprocessing plant in Sellafield site [1,6]. Meanwhile, the total of 1.4x10 14 Bq of Pu radioisotopes was estimated from the reprocessing plant in La Hague site [7]. In addition, the total of 6x10 15 of Pu radioisotopes reported from the nuclear power plant accident in Chernobyl in 1986.…”
Section: Introductionmentioning
confidence: 99%